Cash Waqf Linked Sukuk (CWLS) sebagai Implementasi Filantropi Islam Berkelanjutan - Alfidhatun, Siti (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2024)
Cash Waqf Linked Sukuk (CWLS) is an innovative instrument of state sukuk with waqf. The novelty of this innovation needs to be analyzed for the distribution of funds and their usefulness. The purpose of this research is to analyze the impact of CWLS in Islamic philanthropy. This research uses qualitative methods with library research. The data obtained comes from OJK financial reports, journals, articles, and documents related to CWLS. The results of this study show that the first series of CWLS (SW0001) was used for the development of the Retina and Glaucoma center at Achmad Wardi Eye Hospital, Serang, Banten Province. This is in accordance with Islamic philanthropy as a form of social and sustainable generosity.